Organizational and financial transparency in the website of the foundations: an empirical study for Spain - del Campo Moreno, Paloma; Herrador Alcaide, Teresa C.; Segovia San Juan, Ana I. (REVESCO. Revista de Estudios Cooperativos, 2015)
Transparency in nonprofit sector and foundations, as an element to enhance the confidence of stakeholders in the organization, is a fact shown by several studies in recent decades. Transparency can be considered in various fields and through different channels. In our study we focused on the analysis of the organizational and economic transparency of foundations, shown through the voluntary information on their Website. We review the theoretical previous studies published to put to the foundations within the framework of the social economy. This theoretical framework has focused on accountability that make foundations in relation to its social function and its management, especially since the most recent focus of information transparency across the Website.In this theoretical framework was made an index to quantify the voluntary information which is shown on its website. This index has been developed ad hoc for this study and applied to a group of large corporate foundations.With the application of these data are obtained two kind of results, to a descriptive level and to a inferential level.We analyzed the statistical correlation between economic transparency and organizational transparency offered in the Website through quantified variables by a multiple linear regression. This empirical analysis allows us to draw conclusions about the level of transparency offered by these organizations in relation to their organizational and financial information, as well as explain the relation between them.
Keywords: Social economy; Non-profit organizations; Third sector; Internet; Transparency.